Shaping the future of mental health care - Westlake, Robert J., 1935-; Butler Hospital (Cambridge, Mass. : Ballinger, 1976)
Papers printed at the symposium held at Butler Hospital, Providence, R.I., Spring 1975.
Papers delivered at a two-day symposium entitled "Shaping the future: funding and planning for mental health care," held at Butler Hospital, Providence, R. I., Spring 1975.
Includes bibliographies.
Keywords: Community Mental Health Services -- United States; Health Planning -- United States; Insurance, Psychiatric -- United States; Congresses